Semiconductor physics : principles, theory and nanoscale - Tiwari, Sandip, 1955- (Electroscience series ;, 2020)
"Principles, theory and nanoscale covers the central topics of the field, together with advanced topics related to the nanoscale and to quantum confinement, and integrates the understanding of important attributes that go beyond the conventional solid-state and statistical expositions. Topics include the behavior of electrons, phonons and photons; the energy and entropic foundations; bandstructures and their calculation; the behavior at surfaces and interfaces, including those of heterostructures and their heterojunctions; deep and shallow point perturbations; scattering and transport, including mesoscale behavior, using the evolution and dynamics of classical and quantum ensembles from a probabilistic viewpoint; energy transformations; light-matter interactions; the role of causality; the connections between the quantum and the macroscale that lead to linear responses and Onsager relationships; fluctuations and their connections to dissipation, noise and other attributes; stress and strain effects in semiconductors; properties of high permittivity dielectrics; and remote interaction processes. The final chapter discusses the special consequences of the principles to the variety of properties (consequences of selection rules, for example) under quantum-confined conditions and in monolayer semiconductor systems. The text also bring together short appendices discussing transform theorems integral to this study, the nature of random processes, oscillator strength, A and B coefficients and other topics important for understanding semiconductor behavior. The text brings the study of semiconductor physics to the same level as that of the advanced texts of solid state by focusing exclusively on the equilibrium and off-equilibrium behaviors important in semiconductors"--Publisher's description